Perancangan Antarmuka Aplikasi Mobile Perguruan Tinggi Menggunakan Kansei Engineering (Studi Kasus: STIS Nahdatul Ulama Cianjur) - Alpiyasin, Feri (Jurnal Manajemen Informatika JAMIKA, 2024)
Mobile Apps program-based has given a major influence towards the education sector, specifically in general information about college, especially in stakeholder needs. On the other hand, it also assists in reading the latest events and news, the notification of class schedules, also the information of grades and attendances. The focus of this research is to analyze user preferences including increasing user satisfaction, user retention and design preferences for the interface of Sekolah Tinggi Ilmu Syariah Nahdatul Ulama College mobile app using the Kansei Engineering Type 1 method. The study used Kansei engineering method was conducted to analyze various emotional factors relating to the interface of users by comparing five specimens of college’s mobile apps. A total of twenty kansei words were found from thirty Kansei words based on the selection of UI/UX experts. The data obtained is then analyzed using multivariate statistical methods, such as Cronbach's Alpha (CA), Coefficient Correlation Analysis (CCA), and Factor Analysis (FA). The result is four Kansei words that are influential and have the greatest value, namely Dynamic, Impressive, Professional, and Formal. One selected Kansei word produces recommendations for the appearance of the mobile application interface Sekolah Tinggi Ilmu Syariah Nahdatul Ulama The analysis was conducted on all participants with a focus on the "Formal" emotion concept.